The effect of symmetry on the recognition accuracy of patterns of different complexity - Gurčinienė, Ona; Šoliūnas, Alvydas (Psichologija, 2001)
Symmetry is one of the most important determinants of visual perception. The influence of pattern symmetry on their recognition accuracy was investigated in the psychophysical experiment on human subjects under the conditions of backward masking. A rectangular frame of twelve line segments of equal length was used as a masking pattern (MP). The test patterns (TPs), nonverbal figures were the parts of MP composed by joining four, six, or eight line segments. Five figure sets consisting of equal number of symmetrical and asymmetrical figures of different complexity were used in the experiment. TP was presented for 10 ms, followed by MP for 500 ms with interstimulus interval, which was established for each subject individually as the shortest interval permitting 50-90 proc. recognition accuracy. Each subject took part in four to six test trial sessions. In each trial session, the equal number of symmetrical and asymmetrical figures composed by the same number of line segments was presented for recognition. Experimental data have demonstrated that effect of symmetry on pattern recognition depends on the number of pattern components. The asymmetrical figures consisting of four and six line segments were recognised more accurately than symmetrical ones, whereas the asymmetrical figures consisting of eight line segments have had the lower recognition accuracy than symmetrical ones. Experimental results were interpreted on the basis of optimal relation between the number of elements and symmetry that enables the greatest recognition probability of visual patterns.